2020
DOI: 10.1007/s00381-020-04607-5
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a semiautomated volumetric approach for fetal neurosonography using 5DCNS+ in clinical data from > 1100 consecutive pregnancies

Abstract: Objective The aim of this study was to evaluate the validity of a semiautomated volumetric approach (5DCNS+) for the detailed assessment of the fetal brain in a clinical setting. Methods Stored 3D volumes of > 1100 consecutive 2nd and 3rd trimester pregnancies (range 15-36 gestational weeks) were analyzed using a workflow-based volumetric approach 5DCNS+, enabling semiautomated reconstruction of diagnostic planes of the fetal central nervous system (CNS). All 3D data sets were examined for plane accuracy, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 26 publications
0
13
0
1
Order By: Relevance
“…The latter working group documented successful visualisation rates of 97.7 – 99.4% for axial, 94.4 – 97.7% for sagittal and 92.2 – 97.2% for coronal planes in a prospective follow-up study using the 5DCNS+ modified algorithm 67 . A retrospective clinical validation study of more than 1100 pregnant women yielded similar results 68 . In contrast to the data of Pluym et al, the authors were able to show in their study, among other things, that this standardised approach could be used to collect biometric parameters that, in comparison, were similarly valid and reproducible to those obtained manually 69 .…”
Section: Ai In Standardised Diagnostics Of the Foetal Cnsmentioning
confidence: 74%
See 1 more Smart Citation
“…The latter working group documented successful visualisation rates of 97.7 – 99.4% for axial, 94.4 – 97.7% for sagittal and 92.2 – 97.2% for coronal planes in a prospective follow-up study using the 5DCNS+ modified algorithm 67 . A retrospective clinical validation study of more than 1100 pregnant women yielded similar results 68 . In contrast to the data of Pluym et al, the authors were able to show in their study, among other things, that this standardised approach could be used to collect biometric parameters that, in comparison, were similarly valid and reproducible to those obtained manually 69 .…”
Section: Ai In Standardised Diagnostics Of the Foetal Cnsmentioning
confidence: 74%
“…Letztere Arbeitsgruppe konnte in einer prospektiven Folgestudie mit der Programmerweiterung 5DCNS+ erfolgreiche Visualisierungsraten von 97,7 bis 99,4% für axiale, 94,4 bis 97,7% für sagittale und 92,2 bis 97,2% für koronale Ebenen dokumentieren 67 . Zu ähnlichen Ergebnissen kam auch eine retrospektive klinische Validierungsstudie an mehr als 1100 Schwangeren 68 . Im Gegensatz zu den Daten von Pluym et al konnten die Autoren in ihrer Studie u. a. zeigen, dass mit diesem standardisierten Ansatz vergleichbar valide und reproduzierbare biometrische Parameter wie im Vergleich zu manuellem Vorgehen erhoben werden können 69 .…”
Section: Ki In Der Standardisierten Diagnostik Des Fetalen Znsunclassified
“…3 gives an overview of the detection accuracy and the GA range. 23 , 28 , 33 , 34 , 37 , 59 , 60 , 61 , 62 , 63 , 64 The best results for the TT plane were achieved by Kong et al. and the best results for the TC and TV plane were achieved by Sridar et al.…”
Section: Resultsmentioning
confidence: 98%
“…28 Qualitative and quantitative studies of cortical development evaluation using volume data sets clearly showed the potential of multiplanar assessment and con rmed 3D US as a robust diagnostic method. 14,29,30 Detailed prenatal judgment of even subtle changes in terms of cortical grading and sulci shape and depth is feasible [31][32][33][34] , but it necessitates exact image alignment and, more strikingly, an awareness of the adequacy of planar image adjustment based on anatomical landmarks, as described in the current literature. 29,35 In fact, quite a number of the studies analyzed volume information derived from transvaginally acquired 3D datasets, as these showed a higher image resolution (through US propagation via the sagittal suture and subsequent volume postprocessing).…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been shown that automated volumetric approaches e ciently enable rapid and standardized evaluation of the fetal brain in terms of basic examination [41][42][43] or reconstruction of an entire neurosonogram. [12][13][14] By simplifying the evaluation process of basic and/or advanced CNS examination, these algorithms might aid in earlier detection of abnormal CNS anatomy in utero. However, it remains widely unclear how these automatic techniques are of clinical use in delineating different CNS lesions by means of proper plane reconstruction and visualization of structural defects in detail.…”
Section: Discussionmentioning
confidence: 99%